Adjusting to errors in arithmetic: a longitudinal investigation of metacognitive control in 7–9-year-olds - Jacobs, Eveline; Bellon, Elien; De Smedt, Bert (Frontiers in Developmental Psychology, 2024)
Monitoring and controlling one's performance are essential skills for children's cognitive development and academic success. Metacognitive control, operationalized as post-error adjustments, is, however, often measured in conflict tasks, but the findings of such studies may not be readily generalizable to academic domains, such as arithmetic. Yet, investigating how children control their performance in arithmetic is crucial in understanding the large individual differences within this specific academic domain. This longitudinal study investigated how children control their performance through post-error slowing and accuracy improvement in arithmetic. We additionally examined this development of metacognitive control in a working memory task, to further unravel its domain-generality or the lack thereof. A cohort of 127 typically developing children, followed up longitudinally from 7-8 years old (2 nd grade of primary school) to 8-9 years old (3 rd grade of primary school), completed an arithmetic and working memory task at two time points. Meticulous comparison of response times and accuracy rates following errors with those following correct answers revealed the presence of metacognitive control at each time point. We observed significant positive correlations between children's metacognitive control and their arithmetic accuracy at 7-8 years old, underscoring a possible adaptive role of metacognitive control in the learning phase of arithmetic. No correlations were found between the post-error adjustments in the arithmetic task and those in the working memory task, challenging previous evidence for domain-generality of post-error adjustments.